Reservoir Studies of the Seltjarnarnes Geothermal Field, Iceland - Tulinius, H.; Spencer, A.L.; Bodvarsson, G.S.; Kristmannsdottir, H.; Thorsteinsson, T.; Sveinbjornsdottir, A.E. (Iceland National Energy Authority, Orkustofnun, Geothermal Division, Grensasvegur 9, 108 Reykjavik, Iceland, 1987)
The Seltjarnarnes geothermal field in Iceland has been exploited for space heating for the last 16 years. A model of the field has been developed that integrates all available data. The model has been calibrated against the flow rate and pressure decline histories of the wells and the temperature and chemical changes of the produced fluids. This has allowed for the estimation of the permeability and porosity distribution of the system, and the volume of the hot reservoir. Predictions of future reservoir behavior using the model suggest small pressure and temperature changes, but a continuous increase in the salinity of the fluids produced. 10 figs., 23 refs.